IFSG: Intelligence agriculture crop-pest detection system using IoT automation system - Imrus Salehin; S. M. Noman; Baki Ul-Islam; Israt Jahan Lopa; Prodipto Bishnu Angon; Ummya Habiba; Nazmun Nessa Moon (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The agricultural and technological combination is blessed for modern world life. Internet of things (IoT) is essential for comfort and development to our agriculture side. In our study, we detected the various pest using different types of sensors and this information has automatically sent to the farmer's mobile for the alert. All these sensors had a central database. Those sensors collect all the data and display the results compared to the central data. The High-image sensor will be able to detect all the rays emitted from the plant and another one is the gas sensor which is able to detect all the gases coming from the diseased plant. We mainly use sound sensor, MQ138, CMOSOV-7670, AMG-8833 for a better automation system. We test it with real-time environment conditions (40°C≤TA≤14°C). Crop pest detection automatic process is more efficient than the other detection process according to testing output. As a result, far-reaching changes in the agricultural sector are possible. To reduce extra cost and increasing more farming ability we need to IoT and Agriculture combinations more.